A king amongst dwarfs: Boletus edulis forms ectomycorrhiza with dwarf willow in the Swiss Alps - Treindl, Artemis D.; Leuchtmann, Adrian; id_orcid:0 000-0002-9070-0902 (Springer, 2019)
ISSN:1664-2201 ISSN:1664-221X